Living kidney donation in a developing country - Chandni Dayal; Malcolm Davies; Nina Elisabeth Diana; Anthony Meyers (PLoS ONE, 2022)
Background Living kidney donation has been advocated as a means to ameliorate the chronic shortage of organs for transplantation. Significant rates of comorbidity and familial risk for kidney disease may limit this approach in the local context; there is currently limited data describing living donation in Africa. Methods We assessed reasons for non-donation and outcomes following donation in a cohort of 1208 ethnically diverse potential living donors evaluated over a 32-year period at a single transplant centre in South Africa. Results Medical contraindications were the commonest reason for donor exclusion. Black donors were more frequently excluded (52.1% vs. 39.3%; p<0.001), particularly for medical contraindications (44% vs. 35%; p<0.001); 298 donors proceeded to donor nephrectomy (24.7%). Although no donor required kidney replacement therapy, an estimated glomerular filtration rate below 60 ml/min/1.73 m2 was recorded in 27% of donors at a median follow-up of 3.7 years, new onset albuminuria >300 mg/day was observed in 4%, and 12.8% developed new-onset hypertension. Black ethnicity was not associated with an increased risk of adverse post-donation outcomes. Conclusion This study highlights the difficulties of pursuing live donation in a population with significant medical comorbidity, but provides reassurance of the safety of the procedure in carefully selected donors in the developing world.